UV-vis spectroscopic study of lipid peroxidation and antioxidant contents of kidney of Albino mice co-administrated with sildenafil citrate and alcohol. Issue 4 (2011) - Soumya, K.; Udayakumar, Raju; Viswanathan, K.
Abstract : Male Wistar Albino mice were co-administrated with appropriate dose of sildenafil citrate and alcohol. The kidney samples of those animals were analyzed for lipid peroxidation and antioxidant contents. Lipid peroxidation was measured based on TBARS. Antioxidant such as SOD, CAT, GPx and GSH were also determined. From the present investigation, an enhanced level of TBARS accompanied by a decreased concentration of enzymic as well as non-enzymic antioxidants in kidney was detected for 30 days animals treated concomitantly with sildenafil citrate and alcohol. Increased level of lipid peroxidation lead to accumulation of free radicals and increased oxidative threat in kidney tissues. Also, the decreased concentration of antioxidant enzymes in renal tissues indicates the failure of antioxidant defence system.